Video observation for designers: a contextual immersion of the O&G mannequin in clinical training - Ramli, Saiful Hasley; Rejali, Zulida; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal (Universiti Putra Malaysia Press, 2018)
The use of mannequin is essential in the training of future Obstetrics and Gynaecology (O&G) doctors as it allows them to gain crucial practical experience in conducting medical procedures before performing these procedures on live patients. Despite of the beneficial technology and design emphasised on the existing mannequin used in the O&G domain, propositions have been made by the O&G experts for a new mannequin to be designed. This proposition was therefore addressed through a co-design project. The Contextual Immersion from Mocking-Up co-design approach was used in this project as it suits the designer-clinical expert co-creation circumstances, and it also enables designers to understand the specific user context. This paper reported the process of preparing video observation for designers as a tool in understanding the context in which the O&G mannequin is used in clinical training. Eight different sessions of clinical simulation were video recorded and analysed in this study. These videos used by designers to provide insights to the respective context such as understanding the usage of relevant mannequin in training medical student. Secondly, the video showed the interaction between the expert and novice users to the mannequin. These factors helps the designers to address the related design issues.